Αβ′‐NAC cooperates with Sam37 to mediate early stages of mitochondrial protein import. (12th February 2017) - Ponce‐Rojas, José Carlos; Avendaño‐Monsalve, Maria Clara; Yañez‐Falcón, Armando Roberto; Jaimes‐Miranda, Fabiola; Garay, Erika; Torres‐Quiroz, Francisco; DeLuna, Alexander; Funes, Soledad
Abstract : The mitochondrial proteome is mostly composed of nuclear‐encoded proteins. Such polypeptides are synthesized with signals that guide their intracellular transport to the surface of the organelle and later within the different mitochondrial subcompartments until they reach their functional destination. It has been suggested that the nascent‐polypeptide associated complex (NAC) – a cytosolic chaperone that recognizes nascent chains on translationally active ribosomes – has a role in the import of nuclear‐encoded mitochondrial proteins. However, the molecular mechanisms that regulate the NAC‐mediated cotranslational import are still not clear. Here, we show that a particular NAC heterodimer formed by subunits α and β′ in Saccharomyces cerevisiae is specifically involved in the process of mitochondrial import and functionally cooperates with Sam37, an outer membrane protein subunit of the sorting and assembly machinery complex. Mutants in both components display growth defects, incorrectly accumulate precursor forms of mitochondrial proteins in the cytosol, and have an altered mitochondrial protein content. We propose that αβ′‐NAC and Sam37 are members of the system that recognizes mitochondrial proteins at early stages of their synthesis, escorting them to the import machinery of mitochondria. Abstract : Mitochondrial protein import is facilitated at a cotranslational level with the help of the cytosolic chaperone nascent‐polypeptide associated complex (NAC). In yeast there are two forms of this complex, namely αβ‐NAC and αβ′‐NAC. Each one can physically interact with different receptors at the outer mitochondrial membrane, such as Om14, Tom70 and Sam37, to support early stages of mitochondrial protein biogenesis.